2020
DOI: 10.3389/fchem.2020.00277
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Shift Bonding in Xenon Hydrides: An NBO/NRT Investigation on HXeY···HX (Y = Cl, Br, I; X = OH, Cl, Br, I, CCH, CN) via H-Xe Blue-Shift Phenomena

Abstract: Noble-gas bonding represents curiosity. Some xenon hydrides, such as HXeY (Y = Cl, Br, I) and their hydrogen-bonded complexes HXeY•••HX (Y = Cl, Br, I; X = OH, Cl, Br, I, CN, CCH), have been identified in matrixes by observing H-Xe frequencies or its monomer-to-complex blue shifts. However, the H-Xe bonding in HXeY is not yet completely understood. Previous theoretical studies provide two answers. The first one holds that it is a classical covalent bond, based on a single ionic structure H-Xe + Y −. The second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…This method allowed the synthesis, for example, of the first ever compound of argon: the HArF molecule [ 11 , 12 ]. From quantum-mechanical simulations, it is known that the atoms in the positive (H–Ng) part are covalently bonded [ 4 , 7 , 9 , 13 , 14 , 15 , 16 ], although this can be described as a charge-shift bond [ 15 ]. The bonding between the (H–Ng) moiety and the negative Y moiety is predominantly of ionic nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method allowed the synthesis, for example, of the first ever compound of argon: the HArF molecule [ 11 , 12 ]. From quantum-mechanical simulations, it is known that the atoms in the positive (H–Ng) part are covalently bonded [ 4 , 7 , 9 , 13 , 14 , 15 , 16 ], although this can be described as a charge-shift bond [ 15 ]. The bonding between the (H–Ng) moiety and the negative Y moiety is predominantly of ionic nature.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, xenon forms a large number of compounds and complexes compared to other noble-gas elements, including the HXeY family of compounds: among these, the HXeOH molecule has been studied extensively [ 10 , 14 , 17 , 18 , 19 , 31 ]. The different properties of other complexes have also received considerable attention, both experimentally and computationally: the reported studies include HXeCl/Br/I⋯H O [ 32 , 33 ], HXeCl/Br⋯HCl/Br [ 20 , 34 ], HXeI⋯HBr/I [ 35 ], HXeI⋯HCl and HXeI⋯HCCH [ 36 ], (HXeF) and (HXeF) [ 37 ], HXeF⋯HF [ 13 , 34 , 38 ], HXeBr/Cl⋯HCl/Br and HXeCCH⋯CO [ 14 ], HXeBr⋯CO [ 39 ], HXeSH⋯H O/H S [ 40 ], and HXeOH⋯H S. Recently, Zhang et al [ 15 ] investigated a large set of systems, i.e., HXeY⋯HX (Y = Cl/Br/I and X = OH/Cl/Br/I/CCH/CN), and established the charge-shift nature of the H-Xe bonding in the noble-gas molecule.…”
Section: Introductionmentioning
confidence: 99%
“…However, we anticipate that CS bonding should also be important in understanding Cu/Ag/Au bonding based on some studies by Shaik et al. The CS bond belongs to a new class of chemical bonds, emerging from the valent bond (VB) theory, and it is supported by the atoms in molecules (AIM) theory. Since 1992, this model has been successfully applied to understand the bonding in diatomic halogen molecules (e.g., F 2 ), hypermolecules (e.g., Cl 3 – and XeF 2 ), , transition metal species (e.g., Au 2 and MX), , etc. Our recent study on xenon hydrides using NBO/NRT analyses demonstrated that the H–Xe bonds in all studied molecules exhibit a CS bonding character . In comparison to the CS bonding model, ω-bonding is also one quantum chemically derived model.…”
mentioning
confidence: 95%
“…In recent decades, two new resonance bonding models, charge-shift (CS) bonding and ω-bonding, which involve the delocalization of σ-electrons have been proposed. These two models have been proven valuable in understanding bonding and rationalizing stability of some novel molecules, such as the three-center (3c), four-electron (4e) hypervalent molecule HXeF. , Coincidentally, Legon et al prepared many 3c/4e transition metal complexes BMX (where B is a small Lewis base, M is a coinage metal atom, and X is a halogen atom) in matrix and characterized them using rotational spectroscopy. Their studies provide opportunities to probe the relation between the ω-bonding model and CS bonding model by examining the Cu/Ag/Au bonding in BMX complexes.…”
mentioning
confidence: 99%
See 1 more Smart Citation